Evaluasi Kebijakan Penyelenggaraan Hari Bebas Kendaraan Bermotor (Car Free Day) Di Kota Malang - Sekarsari, Retno Wulan; Suyeno, Suyeno (JU-ke: Jurnal Ketahanan Pangan, 2018)
The Malang City has been carrying out a Car Free Day program since 2011 which is held every Sunday at 5:30 to 10:00 which aims to reduce the use of motorized vehicles in the city of Malang, with the reduced use of motorized vehicles which hopefully can reduce the level of air pollution in the city Malang, especially on Jalan Idjen which is a vital area for many motorized vehicles every day. However, every policy that is implemented by the government cannot be perfectly perfect especially in its implementation and always has advantages and disadvantages. In this study using descriptive - qualitative research methods. The process of collecting data is obtained from 3 ways, namely in-depth interviews with related parties, observation and collection of related documents. Car Free Day implementation that has been implemented by the government in accordance with the Governor Regulation No. 12 of 2016 in which the Car Free Day is held on Sundays from 05:30 to 10:00. the results of Car Free Day activities were able to reduce vehicle users in the city of Malang besides that from the Car Free Day activities were also able to improve the economy of traders who sell in the area of Car Free Day. However, there are still some shortcomings of the management of Car Free Day, such as rubbish on Jalan Idjen caused by visitors and traders, the emergence of several congestion points due to Jalan Idjen being closed. Therefore, this study aims to evaluate the policy of Car Free Day which is carried out along Jalan Idjen Malang. This evaluation is related to how the implementation of Car Free Day in the City of Malang, the impact of the Car Free Day program to the policies applied by agencies related to the procurement of Car Free Day in the City of Malang.